Fimbrolide Natural Products Disrupt Bioluminescence of Vibrio By Targeting Autoinducer Biosynthesis and Luciferase Activity. Issue 3 (26th November 2015) - Zhao, Weining; Lorenz, Nicola; Jung, Kirsten; Sieber, Stephan A.
Abstract: Vibrio is a model organism for the study of quorum sensing (QS) signaling and is used to identify QS‐interfering drugs. Naturally occurring fimbrolides are important tool compounds known to affect QS in various organisms; however, their cellular targets have so far remained elusive. Here we identify the irreversible fimbrolide targets in the proteome of living V. harveyi and V. campbellii via quantitative mass spectrometry utilizing customized probes. Among the major hits are two protein targets with essential roles in Vibrio QS and bioluminescence. LuxS, responsible for autoinducer 2 biosynthesis, and LuxE, a subunit of the luciferase complex, were both covalently modified at their active‐site cysteines leading to inhibition of activity. The identification of LuxE unifies previous reports suggesting inhibition of bioluminescence downstream of the signaling cascade and thus contributes to a better mechanistic understanding of these QS tool compounds. Abstract : Studies in Vibrio : Fimbrolides represent natural products that interfere with quorum sensing in various organisms. Despite their importance in biological studies their cellular mechanisms have remained unknown. Chemical proteomics have been utilized to identify proteins involved in autoinducer biosynthesis (LuxS) and luciferase activity (LuxE) as molecular targets.